Kultur Pernikahan Jawa dalam Hitungan Weton Perspektif Hukum Islam - Isnaini Nur Nabila Firdaus; Nizar Zulmi (JASNA : Journal For Aswaja Studies, 2023)
AbstractThis study aims to examine and analyze Javanese wedding culture related to the practice of counting weton from the perspective of Islamic law. Through a descriptive-analytical approach, data was collected through literature studies and field observations to understand how Javanese people use weton in choosing a spouse. The results of the study show that in Javanese wedding culture, weton count is considered important as a consideration in choosing a partner. However, the determination of weton must pay attention to the limitations of Islamic law. Religious principles such as religious compatibility, morality, and values that are upheld in Islam must still be prioritized in choosing a partner. In addition, this study also highlights the importance of tolerance and good morals in responding to various social problems. Even though the practice of counting weton is still carried out, it should be remembered that the success of a marriage does not only depend on weton alone. Good communication, mutual understanding, commitment, and joint efforts also play an important role in building a happy and successful marriage. This research provides insight into how Javanese wedding culture and the practice of counting weton can be understood from the perspective of Islamic law. It is hoped that the results of this research can become the basis for promoting a balanced understanding between cultural traditions and religious values in the context of marriage in Javanese society, taking into account Islamic religious principles as the main guideline.Keywords: Javanese Culture, Marriage, Weton, Islamic Law.AbstrakPenelitian ini bertujuan untuk mengkaji dan menganalisis kultur pernikahan Jawa terkait dengan praktik hitungan weton dari perspektif hukum Islam. Melalui pendekatan deskriptif-analitis, data dikumpulkan melalui studi pustaka dan observasi lapangan untuk memahami bagaimana masyarakat Jawa menggunakan weton dalam pemilihan pasangan hidup. Hasil penelitian menunjukkan bahwa dalam kultur pernikahan Jawa, hitungan weton dianggap penting sebagai pertimbangan dalam memilih pasangan. Namun, penentuan weton harus memperhatikan batasan-batasan syariat Islam. Prinsip-prinsip agama seperti kompatibilitas agama, moralitas, dan nilai-nilai yang dijunjung tinggi dalam Islam harus tetap diutamakan dalam pemilihan pasangan. Selain itu, penelitian ini juga menyoroti pentingnya sikap toleransi dan akhlakul karimah dalam menyikapi berbagai persoalan kemasyarakatan. Meskipun praktik hitungan weton masih dilakukan, tetapi perlu diingat bahwa keberhasilan pernikahan tidak hanya bergantung pada weton semata. Komunikasi yang baik, saling pengertian, serta komitmen dan upaya bersama juga memiliki peran penting dalam membangun pernikahan yang bahagia dan sukses. Penelitian ini memberikan wawasan tentang bagaimana kultur pernikahan Jawa dan praktik hitungan weton dapat dipahami dari perspektif hukum Islam. Diharapkan hasil penelitian ini dapat menjadi dasar untuk mempromosikan pemahaman yang seimbang antara tradisi budaya dan nilai-nilai agama dalam konteks pernikahan di masyarakat Jawa, dengan memperhatikan prinsip-prinsip agama Islam sebagai pedoman utama.Kata Kunci: Kultur Jawa, Pernikahan, Weton, Hukum Islam.